Atmospheric-Pressure Non-thermal Plasma-JET effects on PS and PE surfaces - Arrieta, J.; Asenjo, J.; Solís, Y.; Vargas-Blanco, Iván (Institute of Physics Publishing, 2015)
The Atmospheric-Pressure Non-Thermal Plasma (APNTP) has become a topic of a great interest for a wide spectrum of applications in different industry branches, including the surface of treatment processes. In this work we evaluate the effect of an argon APNTP exposure to determine changes suffered by a polystyrene (PS) and polyethylene (PE) polymer surface through RAMAN spectroscopy and SEM. It was determined that the hydrophilic change in energetic terms, i.e. surface activation in the PS and PE polymers is addition of oxygen by surface activation when the samples with jet plasma are exposed with the inert argon gas. It was possible to characterize the hydrophilic shift based on the change in intensity of the spectra. © Published under licence by IOP Publishing Ltd.
https://www.scopus.com/inward/record.url?eid=2-s2.0-84938125206&partnerID=40&md5=c2325a28f944e7e3e20b601b8d9a73ef
Keywords: Argón; Presión atmosférica; Plasma; Research Subject Categories::TECHNOLOGY::Engineering physics::Plasma physics with fusion